Struktur Pembiayaan UMKM di Kota Pontianak Pasca Kenaikan Harga BBM Mei 2008 - Anwar Azazi, Erdy, Rizki Fauzan, dan Juniwati, . (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2010)
ABSTRACT The main objective of this study is to shed lights on the MSMEs’ financial structure in Pontianak Municipality following the rise in oil price in May 2008. The research methodology used is survey method through structured interview undertaken in September and October 2008 for a selected sample of 40 MSMEs comprising small industry, retail trading, small restaurant, and services sectors in four sub-districts in Pontianak municipality. Collected data is then analyzed qualitatively. The results of research show that MSMEs’ financial structure mostly consists of equity, followed by loan from rent hunters, and a mix of equity and debt. Three months following the rise in oil price, 60% of MSMEs had only realized sales less than Rp50 million. Retail business sector and small restaurant underwent little impact on its sales, even some enjoyed sales increasing. Quartely Earning Before Interest and Taxes (EBIT) following the rise of oil price earned by most SMEs (67,50%) was by average less than Rp25 million.   Keywords:  financial structure, SMEs, oil price escalation